Prevalence of Post-Partum Depression in India and Its Association with Risk Factors: A Systematic Review and Meta-Analysis - Gupta, Bhupesh; Grover, Kashish; Gupta, Shivashish; Gupta, Kirtika; Goel, Ramita; Mittal, Anshu (National Journal of Community Medicine, 2025)
Introduction: This study uses an exhaustive meta-analysis of descriptive epidemiological studies to determine the prevalence of major depression in post-partum females and its associated risk factors, across all ages in India. Methodology: Using PRISMA guidelines, we searched PubMed, Scopus, Web of Science, Embase, and Google Scholar for studies from 2020–2024. The review was registered in PROSPERO (CRD42024513914). Eligible English-language observational studies reported depression prevalence in perinatal Indian women. Meta-analysis was done using R (v4.3.0), and study quality was assessed with the JBI score. Pooled prevalence and odds ratios with 95% CI were calculated. Heterogeneity was evaluated using Q and I² statistics, and publication bias was assessed with Egger’s test and a funnel plot. Results. Utilizing a random effects model, the results of 59 publications were used to estimate the prevalence of post-partum depression in India from 2020-2024 to be 19% (CI = 95: 15–23%). Meta-regression analysis found that older age post-partum females had a higher prevalence of post-partum depression as compared to young ones. Heterogeneity for prevalence was found to be 97%. The sub-group analysis found a higher prevalence of post-partum depression in Southern India (22%; 95% CI: 15–31), studies conducted in community settings (19%; 95% CI: 12–28), urban areas (19%; 95% CI: 15–24), studies using study instruments other than EPDS scale (22%; 95%CI: 11–39), and publication year 2024 (25%; 95% CI: 17-36). Conclusion. Effective measures like psychological counselling and health education, need to be taken to control post-partum depression in India.